Quality Assurance of Nursing Performance in Surgical Wards - Allah, bushra; AI-Gersha, Khalida; Al-Gailani, Saieb (Iraqi National Journal of Nursing Specialties, 2007)
Objective: The study deafs with nursing performance in the surgical wards in general hospital at Baghdad city. Methodology : A descriptive evaluation design using, observational method was carried out. Non probability (purposive) sample of (151) nurses was selected for the study and comprised all nurses who worked in general surgical wards in the four health sectors( Rusaffa , Al-Karkh, Al-Yarmok, Medical city health sector) at time of collecting the data. A check list questionnaire was constructed by the researcher for the purpose of the study; it is composed of (2) major parts, part (I) is concerned with socio-demographic data and the second part is composed of two minor parts thev concerned with availability of equipment and nursing performance. Validity of the questionnaire was determined through panel of experts. Reliability of the questionnaire was determined through computation correlation coefficient of (93.3) was statistically acceptable.The data were analyzed through the application of the descriptive data analysis approach and the inferential statistics. Results : The findings of the study indicated that more than half of the sample (66.2%) was male, the majority of the sample (71.52%) were in group (25-30) year. Most of the sample (29.8%) was training course graduates. The higher percentage (58.3%) has no training session after ward. Findings of the study had pointed that there were severe shortages in availability of equipment related to patients admission procedure, preoperative and postoperative nursing care procedures.The results also revealed that the nurses performance were inadequate related to some nursing procedures such as admission procedure, preoperative nursing care procedure and postoperative nursing procedure. The findings of the study has approved that there was significant relationship between nursing performance and demographic variables, Such as gender, age, level of education, training session.